Pendampingan Orang Tua Dalam Pertumbuhan Rohani Remaja - Nurmiati Marbun; Berta Tarigan (KERUGMA: Jurnal Teologi dan Pendidikan Agama Kristen, 2020)
Abstract:Adolescence is a period of transition or transition from childhood to adulthood. At this time, adolescents are often faced with uncertainty regarding their status, on the one hand they are no longer recognized as children, but on the other hand they cannot be said to be adults because they have not been able to fulfill adult duties. This state is also referred to as a time of hurricanes and storms. This uncertainty makes teenagers feel awkward, they don't know what to do in the face of uncertainty. For this reason, assistance from parents is needed for adolescents because this assistance is the main thing for adolescents so that they do not take wrong steps and find what is certain in themselves.Keywords: Parental assistance; spiritual growth; teenager. Abstrak:Masa remaja adalah masa transisi atau masa peralihan dari masa kanak-kanak ke masa dewasa. Pada masa ini remaja seringkali dihadapkan pada ketidakpastian yang berkenaan dengan status mereka, disatu pihak mereka sudah tidak lagi diakui sebagai kanak-kanak, namun dipihak lain mereka belum dapat dikatakan dewasa karena belum mampu memenuhi tugas-tugas orang dewasa. Keadaan ini juga disebut sebagai masa yang penuh topan dan badai. Ketidakpastian ini membuat remaja menjadi salah tingkah, mereka tidak tahu harus berbuat apa dalam menghadapi ketidakpastian itu. Untuk itulah dibutuhkan pendampingan dari orang tua bagi remaja karena pendampingan tersebut adalah hal utama bagi remaja agar tidak salah melangkah dan menemukan yang pasti dalam dirinya.Kata kunci: Pendampingan orang tua;  pertumbuhan rohani; remaja.